A core–shell fiber moisture-driven electric generator enabled by synergetic complex coacervation and built-in potential - Zan, Guangtao; Jiang, Wei; Kim, HoYeon; Zhao, Kaiying; Li, Shengyou; Lee, Kyuho; Jang, Jihye; Kim, Gwanho; Shin, EunAe; Kim, Woojoong; Oh, Jin Woo; Kim, Yeonji; et al. (Nature communications, 2024)
Moisture-driven electricity generators (MEGs) have been extensively researched; however, high-performance flexible variants have seldom been demonstrated. Here we present a novel complex coacervation with built-in potential strategy for developing a high-performance uniaxial MEG, featuring a core of poly(3,4-ethylenedioxythiophene) (PEDOT) with a built-in charge potential and a gel shell composed of poly(diallyldimethylammonium chloride) (PDDA) and sodium alginate (NaAlg) coacervate. The complex coacervation of two oppositely charged polyelectrolytes produces extra mobile carriers and free volume in the device; meanwhile, the PEDOT core’s surface charge significantly accelerates carrier diffusion. Consequently, the uniaxial fiber-based MEG demonstrates breakthrough performance, achieving an output voltage of up to 0.8 V, a maximum current density of 1.05 mA/cm 2 , and a power density of 184 μW/cm 2 at 20% relative humidity. Moreover, the mechanical robustness is ensured for the PEDOT nanoribbon substrate without performance degradation even after 100,000 folding cycles, making it suitable for self-powered human interactive sensor and synapse. Notably, we have constructed the inaugural MEG-synapse self-powered device, with a fiber-based MEG successfully operating a synaptic memristor, thereby emulating autonomous human synapses linked with fibrous neurons. Overall, this work pioneers innovative design strategies and application scenarios for high-performance MEGs. The authors present a core–shell fiber moisture-driven electric generator by a synergetic complex coacervation and built-in potential strategy, enabling self-powered human interactive sensors and synaptic devices.